René Maran à Maurice Barrès : d’un « écrivain français » à l’autre - Xavier Luce (Continents manuscrits)
In the letters addressed to Maurice Barrès the years preceding Batouala, a true black novel publication, between 1917 and 1920, topics of Rene Maran authorial intention and exposure are highlighted. As a matter of fact, it seems writing may have been an ontological imperative, namely the demonstration that “negroes” are men like the others. The author of Un homme pareil aux autres stages himself as a prime example and ambassador of the black civil rights advancement because they are so-called “perfectible beings”. Reading these letters allows us to assess the meaning of his “French writer profession”, the “antiracist fight” he has been able to take part in The universal league for the defense of the negro race. It is in the light of negritude that his involvement could make sense being “a practice without a theory” built upon the “questions raised by the negro presence in the world” and “his perception by others and his self-perception”.